Clear cell adenocarcinoma arising from adenomyotic cyst: A case report and literature review. Issue 2 (4th November 2015) - Baba, Akira; Yamazoe, Shinji; Dogru, Murat; Ogawa, Mariko; Takamatsu, Kiyoshi; Miyauchi, Jun
Abstract: Ovaries are the primary sites of cancerous disease that is derived from endometriosis. Uterine cancer originating from endometriosis is very rare. The most frequent histological subtype of cancer derived from endometriosis is endometrioid adenocarcinoma, a subtype of clear cell carcinoma which is exceedingly rare. We report a case of a 40‐year‐old Japanese woman with a six year history of uterine leiomyoma. The patient was clinically and radiologically suspected to have degenerative uterine myoma with a possible malignant association and underwent a transabdominal total hysterectomy. Histopathological examination of the specimens revealed clear cell adenocarcinoma arising from the adenomyotic cyst. A literature review of clear cell adenocarcinomas arising from uterine adenomyotic cysts (cystic adenomyosis), emphasizes the clinically and radiologically important features of this very rare entity. Clear cell carcinoma association should be suspected in patients who are under follow‐up for uterine myomas and present with cystic uterine changes with solid component on magnetic resonance imaging or computed tomography scans.